1996
DOI: 10.1172/jci118490
|View full text |Cite
|
Sign up to set email alerts
|

Increased acetyl group availability enhances contractile function of canine skeletal muscle during ischemia.

Abstract: Skeletal muscle contractile function is impaired during acute ischemia such as that experienced by peripheral vascular disease patients. We therefore, examined the effects of dichloroacetate, which can alter resting metabolism, on canine gracilis muscle contractile function during constant flow ischemia. Pretreatment with dichloroacetate increased resting pyruvate dehydrogenase complex activity and resting acetylcarnitine concentration by ‫ف‬ 4-and ‫ف‬ 10-fold, respectively. After 20-min contraction the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
102
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(121 citation statements)
references
References 28 publications
(30 reference statements)
14
102
5
Order By: Relevance
“…However, Gibala, MacLean, Graham & Saltin, (1998) Dichloroacetate infusion results in near-maximal activation of the pyruvate dehydrogenase complex and stockpiling of acetyl-units. During the transition to subsequent moderate intensity exercise, dichloroacetate infusion has consistently been shown to enhance the rate of increase of oxidative metabolism as indicated by a reduction in phosphocreatine degradation and lactate accumulation (Timmons et al 1996;Timmons, Poucher, Constantin-Teodosiu, Macdonald & Greenhaff, 1997;Timmons et al 1998aTimmons, Gustafsson, Sundberg, Jansson & Greenhaff, 1998bHowlett, Heigenhauser, Hultman, Hollidge-Horvat & Spriet, 1999a;Parolin et al 2000;Roberts, Loxham, Poucher, Constantin-Teodosiu & Greenhaff, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, Gibala, MacLean, Graham & Saltin, (1998) Dichloroacetate infusion results in near-maximal activation of the pyruvate dehydrogenase complex and stockpiling of acetyl-units. During the transition to subsequent moderate intensity exercise, dichloroacetate infusion has consistently been shown to enhance the rate of increase of oxidative metabolism as indicated by a reduction in phosphocreatine degradation and lactate accumulation (Timmons et al 1996;Timmons, Poucher, Constantin-Teodosiu, Macdonald & Greenhaff, 1997;Timmons et al 1998aTimmons, Gustafsson, Sundberg, Jansson & Greenhaff, 1998bHowlett, Heigenhauser, Hultman, Hollidge-Horvat & Spriet, 1999a;Parolin et al 2000;Roberts, Loxham, Poucher, Constantin-Teodosiu & Greenhaff, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Classically, the lag in oxidative ATP production and resulting oxygen deficit have been attributed to a lag in muscle blood flow and thereby muscle oxygen delivery, which also follows an approximately exponential time course (21, 30). However, more recently it has been proposed that oxygen availability may not be the sole determinant of the oxygen deficit, at least at submaximal exercise workloads (11,29), such that the delay in mitochondrial energy production must be attributable, at least in part, to a lag in enzyme activation and/or substrate delivery (metabolic inertia) within energy-producing pathways on the initiation of muscular contraction (10,12,18,37).A recent series of studies by our group has demonstrated the existence of metabolic inertia at the onset of contraction (27,28,(33)(34)(35)(36). On the basis of evidence from these studies, we believe that the delay in acetyl-CoA provision at the onset of exercise, which we have termed the "acetyl group deficit" (27), is a principal determinant of the oxygen deficit (27,33,34).…”
mentioning
confidence: 99%
“…Muscle [ATP], [PCr], and lactate efflux during the I condition were not significantly different from the values seen at the same stimulation intensity with normal blood flow. Timmons et al (29) found muscle [PCr] and [ATP] to be significantly more depleted (and found greater lactate accumulation) in contracting muscle when partial ischemia was imposed from the onset of contractions compared with a control condition at the same stimulation frequency but with normal blood flow. It is likely that in the present study, the lack of any significant differences in muscle [PCr], [ATP], and lactate efflux beween the I condition and the same stimulation with normal blood flow was due to the fact that the muscle was in a steady state of contractile activity, with all regulatory enyzmes fully activated, when the partial ischemia was induced.…”
Section: Skeletal Muscle Bioenergetics After Blood Flow Reductionmentioning
confidence: 99%
“…Timmons et al (28)(29)(30) recently demonstrated that substrate availability through the pyruvate dehydrogenase complex (PDC) for carbohydrate oxidation in the tricarboxylic cycle can affect subsequent muscle performance during moderate ischemia. These investigators (30) demonstrated that having the PDC enzyme fully activated at the onset of an ischemic contractile period resulted in significantly less PCr hydrolysis and lactate accumulation and subsequently less fatigue compared with the same ischemic blood flow reduction with PDC starting from the normal resting deactivated state.…”
mentioning
confidence: 99%